The Right to Food, Deliberate Starvation, and the EU’s Response to International Courts’ Rulings - Anna Oriolo (Bulletin of the Transilvania University of Braşov: Series VII: Social Sciences, Law)
This article examines starvation as a crime of global concern, particularly in situations of conflict and humanitarian emergencies, and the European Union’s role in combating this crime. The analysis focuses on the international and European legal framework on the right to food, the impact of armed conflict on this right, and the use of starvation as a method of warfare. The article concludes with a critical assessment of the EU’s response to food security threats, specifically in relation to the recent Israeli-Palestinian crisis.